Effects of the salivary flow rate, pH, viscosity and buffering capacity on dental caries experience in government school children in Bangalore city - B., Annapoorna H.; Datta, Dipayan (International Journal Of Community Medicine And Public Health, 2020)
Background: The present study was undertaken to evaluate effect of the salivary flow rate, pH, viscosity and buffering capacity on caries experience in government school children.Methods: This case-control study was conducted amongst the Government school children of Bangalore city aged 6-14 years. A total of 180 school children were selected out of what 90 were selected for the test group based on the presence of one or more active dental caries and another 90 were selected for the control group who were free of dental caries at the time of examination. Saliva samples were collected from all subjects and were estimated for flow rate, pH, viscosity and buffering capacity.Results: Mean salivary flow rate, pH and buffer capacity have been found to be significantly lower and mean salivary viscosity has been found to be significantly higher among children with dental caries.Conclusions: The physical and biochemical properties of saliva, such as salivary flow rate, pH, buffering capacity and viscosity are significantly related with the caries experience in children.